Macroeconomic Adjustment in a Highly Dollarized Economy : The Case of Cambodia. (IMF Working Papers; Working Paper ;, 2002)
Cambodia became dollarized suddenly in the early 1990s, as a result of massive dollar inflows stemming from a postconflict situation. Considering that the amount of dollars in circulation is unusually high, we attempt to estimate the true degree of dollarization empirically. Our results show that Cambodia has been virtually fully dollarized since 1995. Against a background of severe institutional limitations, the authorities have implemented in recent years policies akin to those of a de facto currency board arrangement, in particular with respect to fiscal discipline. The paper concludes that this policy mix has been appropriate for Cambodia's circumstances.